DYNAMICS OF PANCASILA AS A BASIS FOR THE QUALITY OF INDONESIAN LEGISLATION: A POSITIVE LAW PERSPECTIVE AND THE CONSTITUTIONAL COURT'S DECISION: DINAMIKA PANCASILA SEBAGAI LANDASAN KUALITAS LEGISLASI INDONESIA: PERSPEKTIF HUKUM POSITIF DAN PUTUSAN MAHKAMAH KONSTITUSI - Subawa, Made; Hermanto, Bagus; Giri, Ni Putu Niti Suari (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2025)
This article interrogates the dimensions of the fifth-generation national philosophy of Indonesia, the 'Pancasila', and its potential to serve as the cornerstone for enhancing the quality of legislation in Indonesia. The prevailing concern is that the quality of Indonesian legislation is frequently compromised in terms of material and formal aspects, irrespective of the multidimensional, multidisciplinary, and even cross-border challenges confronting various developing countries. In order to address these concerns, it is imperative to delve into the fundamental principles of the 'Pancasila', with a view to contributing to the development of a future legal framework characterised by enhanced quality. The present article is limited to two main issues, namely (1) the dynamics of the five principles of the Indonesian state ideology as a legal ideal, and (2) the futuristic dimension based on positive law and the Constitutional Court's decisions related to the aforementioned principles as a basis for improving the quality of future legislation. The results obtained demonstrate that the recognition of the inseparable nature of the five principles of the United Nations as a legal ideal and the primary source of national law is paramount. This underscores the necessity for future legislative formations to deliberate on the incorporation of the principles of the Pancasila as a consideration in enhancing the quality of future legislation.